Disease Severity and Depressive Symptoms in Adolescents With Inflammatory Bowel Disease: The Mediating Role of Parent and Youth Illness Uncertainty. (14th December 2018) - Baudino, Marissa N; Gamwell, Kaitlyn L; Roberts, Caroline M; Grunow, John E; Jacobs, Noel J; Gillaspy, Stephen R; Edwards, Clayton S; Mullins, Larry L; Chaney, John M
Abstract: Objective: The objective of this study is to examine parent and youth appraisals of illness uncertainty as potential serial mediators in the relation between disease severity and youth depressive symptoms in adolescents with inflammatory bowel disease (IBD). Methods: Participants were 85 adolescents 13–18 years of age ( M age = 15.75, SD =1.51) with a confirmed diagnosis of IBD (Crohn's disease, 59%; ulcerative colitis, 41%) and a primary caregiver. At a scheduled outpatient visit, caregivers completed a measure of illness uncertainty, while adolescents completed measures of illness uncertainty and depressive symptoms . Pediatric gastroenterologists provided global estimates of disease severity . Results: Path analysis revealed several significant direct and indirect associations among the modeled variables. Importantly, results provided support for the hypothesized disease severity → parent illness uncertainty→youth illness uncertainty→youth depressive symptoms serial mediation path (95% confidence interval = 0.04 to 1.10). Conclusions: Results indicate that increased disease activity may serve to magnify the unpredictable nature of IBD for parents, reflected in heightened perceptions of illness uncertainty. Our findings also suggest that increased parent illness uncertainty has a significant influence on youth illness uncertainty appraisals, which in turn translates into elevated depressive symptoms in adolescents with IBD. The clinical implications of our findings and suggestions for future studies are discussed.